An overview of Mehmet Akif Ersoy’s ideal generation in Âsım - Firuzi, Mortaza (Études sur la Région Méditerranéenne, 2020)
There were four various leading ideas among the Ottoman intellectuals in the late Ottoman Empire: Ottomanism, Islamism, Turkism, and Westernism. As one of the intellectuals, Mehmet Akif Ersoy (1873–1936) emphasized on Islamism and rejected the other ideas based on his experience and thoughts. Hence, in light of his Islamist idea, he created his notable masterpiece Âsım in the sixth volume of Safâhat. It is written based on narrative and dialogue among four people including Hocazâde, Köse İmâm, Emin and Âsım in the Ottoman language. Mehmet Akif Ersoy tried to create an ideal generation and a model for the Ottoman’s people based on the primary sources of Islam which could be applied in the modern world as well. Although the work was written almost a century ago, it has still been considered as an inspiring story among some Turks. This paper attempts to investigate Âsım epos as a one of masterpieces of Mehmet Akif Ersoy in terms of the main characteristics of the ideal generation which was expected to be a model for the future generation of Turks.